Spatial clustering of hosts can favor specialist parasites - Jeremy Draghi; Evan Zook (Ecology and Evolution)
Abstract Generalist parasites seem to enjoy the clear ecological advantage of a greater chance to find a host, and genetic trade‐offs are therefore often invoked to explain why specialists can coexist with or outcompete generalists. Here we develop an alternative perspective based on optimal foraging theory to explain why spatial clustering can favor specialists even without genetic trade‐offs. Using analytical and simulation models inspired by bacteriophage, we examine the optimal use of two hosts, one yielding greater reproductive success for the parasite than the other. We find that a phage may optimally ignore the worse host when the two hosts are clustered together in dense, ephemeral patches. We model conditions that enhance or reduce this selective benefit to a specialist parasite and show that it is eliminated entirely when the hosts occur only in separate patches. These results show that specialists can be favored even when trade‐offs are weak or absent and emphasize the importance of spatiotemporal heterogeneity in models of optimal niche breadth.